OHP-029 Leukocyte radiolabelling settings assessment according to the medical indication. (25th February 2017) - Nachon, P; Dekyndt, B; Legrand, JF; Semah, F
Abstract : Background: Radiolabelled leukocytes are one of the most specific scintigraphy examinations to diagnose deep tissue infection. White blood cells are isolated by sedimentation and centrifugation and then labelled with radioactive drugs. A few checks are performed to evaluate the quality of the labelling before injection. One of these controls consists of determination of labelling yield. The sedimentation volume is another parameter easily measurable and can influence the labelling yield. Purpose: The purpose of the study was to evaluate the correlation between leukocyte radiolabelling settings and the medical scintigraphy indication. Material and methods: An analysis of the radiolabelling settings performed in a nuclear medicine department from December 2013 was completed with XLSTAT 2016. We analysed two major settings: sedimentation volume and radiolabelling yield. Five indications were compared: pacemaker endocarditis (n=15), deep tissue infection (n=40), vascular prosthesis infection (n=23), osteitis and osteoarthritis (n=71) and bone and joint infection on device (n=173). Two studied variables did not follow the normal distribution, and a non-parametric test was performed to compare the two settings according to the indication. Results: A statistically significant difference was found for the radiolabelling yield: bone and joint infection on device was the indication which had the worst labelling yield (52%) compared with the other indications (pacemaker endocarditis (60.2%), deep tissue infection (57%), osteitis and osteoarthritis (56.5%) (p<0.02 except vascular prosthesis infection (56.3%)). There were statistically significant differences for sedimentation volume between the five indications but no indication stood out. The lower labelling yield observed on bone and joint infection on device indication may be explained by the chronic nature of infection. In this indication, antibiotics are often used which cause a decrease in leukocytes in blood. Conclusion: Even if radiolabelling yield differences exist according to the indication, radiolabelling leukocytes is still a specific examination to diagnose infection of deep tissues. Work on optimisation of the sedimentation step and on the labelling temperature are in progress in this department. References and/or acknowledgements: Guide du bon usage des examens d'imagerie médicale, Transposition de la directive européenne 97/43 Euratom, 2005. No conflict of interest